System-Technology Co-Optimization of Multimetal Gated AlGaN/GaN HEMT for Improved RF Linearity - Toiyob Hossain; Tanvir Hossain; A. K. M. Anindya Alam; Bejoy Sikder; Qingyun Xie; Mengyang Yuan; Eiji Yagyu; Koon Hoo Teo; Tomas Palacios; Nadim Chowdhury (IEEE Journal of the Electron Devices Society)
In this work, a system-technology co-optimization (STCO) of the AlGaN/GaN multimetal gated (MMG) HEMT architecture for third-order transconductance (gm3) engineering and linearity improvement in the presence of fermi-level pinning (FLP) is reported. Through technology computer-aided design (TCAD), compact modeling, load-pull simulations and modulated signal simulations, it is shown that despite incorporating FLP, employing MMG scheme improves device level gm3 - suppression, leading to an improvement in output-referred third-order intercept point per unit dc power (OIP3/PDC) and third order intermodulation distortion (IMD3). Remarkably, OIP3/PDC of 18.9 dB is obtained considering an FLP factor of 0.43, which is a 10.7 dB improvement over the conventional HEMT. MMG HEMT exhibits an output-referred 1-dB compression point (P1-dB) of 3.60 W/mm, compared to 0.60 W/mm for the standard/conventional case. A comparative analysis on output power back-off (OBO) for conventional and MMG HEMT with different FLP factors establishes MMG as a robust architecture to FLP. Simulations involving 5G FR1 signals demonstrate that the adjacent channel power ratio (ACPR) is sustained below -40 dBc up to an output power of 20 dBm. 2.6% lower error vector magnitude (EVM) than baseline case is achieved by MMG HEMT at 5 GHz, under 100 MHz 64-QAM OFDM signals.